Primary hepatic angiosarcoma with noncirrhotic portal hypertension: A case report - Wu, Xuwei; Yu, Xia; Gan, Qiaorong; Wang, Bin; Lin, Zhaowang; Shi, Yu; Huang, Zuxiong (Frontiers in Oncology, 2023)
Background Primary hepatic angiosarcoma (PHA) is a rare malignant tumor of mesothelial tissue origin in the liver. The diagnosis of PHA relies on pathology, and it is frequently misdiagnosed as multiple hepatic hemangioma. Noncirrhotic portal hypertension is a relatively rare pathological manifestation, and there are few reports of PHA as an uncommon cause of noncirrhotic portal hypertension. Case summary A 36-year-old male was admitted with abnormal liver function and suspected drug-induced liver injury (DILI), initially manifesting as multifocal hepatic hemangioma. The liver biopsy revealed features of noncirrhotic portal hypertension (NCPH), and the patient was eventually diagnosed with multifocal hepatic angiosarcoma. Conclusion Patients with PHA may present with NCPH in the liver due to injury to hepatic sinusoids; therefore, it is necessary to consider the possibility of unsampled vascular malignancy when hepatic masses are identified, and the histology is consistent with PHA.